Yahuza al-Iskhriyuti (Judas Iscariot) according to the views of Quranic muffassirin scholars - Md. Zain, Aman Daima; Ibrahim, Muhammad Lukman; Mohamed, Hasan Al-Banna; Awang, Jaffary (Online Journal of Research in Islamic Studies, 2015)
Yahuza al-Iskhiriyuti is a name used by Islam in reference to individuals who are not alien to Christianity and have been noted in the books of Bible. Judas Iscariot and Yahuza al-Iskhiriyuti are two names referring to an individual regarded as a traitor by the Christians following his handing over of Jesus Christ to the Jews to be killed and crucified. In Islam, the event of the killing and crucifixion of Isa a.s. as claimed by Christian also narrated by Allah SWT in the Quran. However, Islam has the view that the person murdered and crucified was not Isa a.s., but another person whom Allah SWT created to resemble him. It is just that the identity of the murdered man is only vaguely mentioned by Allah SWT in the Quran. Nonetheless, if we refer to the opinions of the experts, there are several names which can be associated with this particular individual. Therefore, this writing aims at revealing who this figure actually is, from the perspective of the mufassirin also the role he plays in the killing and crucifixion of Jesus Christ.